Manipulation of Cell Cycle and Chromatin Configuration by Means of Cell-Penetrating Geminin. - Yoshinori Ohno; Kyoko Suzuki-Takedachi; Shin'ichiro Yasunaga; Toshiaki Kurogi; Mimoko Santo; Yoshikazu Masuhiro; Shigemasa Hanazawa; Motoaki Ohtsubo; Kazuhito Naka; Yoshihiro Takihara (PLoS ONE)
Geminin regulates chromatin remodeling and DNA replication licensing which play an important role in regulating cellular proliferation and differentiation. Transcription of the Geminin gene is regulated via an E2F-responsive region, while the protein is being closely regulated by the ubiquitin-proteasome system. Our objective was to directly transduce Geminin protein into cells. Recombinant cell-penetrating Geminin (CP-Geminin) was generated by fusing Geminin with a membrane translocating motif from FGF4 and was efficiently incorporated into NIH 3T3 cells and mouse embryonic fibroblasts. The withdrawal study indicated that incorporated CP-Geminin was quickly reduced after removal from medium. We confirmed CP-Geminin was imported into the nucleus after incorporation and also that the incorporated CP-Geminin directly interacted with Cdt1 or Brahma/Brg1 as the same manner as Geminin. We further demonstrated that incorporated CP-Geminin suppressed S-phase progression of the cell cycle and reduced nuclease accessibility in the chromatin, probably through suppression of chromatin remodeling, indicating that CP-Geminin constitutes a novel tool for controlling chromatin configuration and the cell cycle. Since Geminin has been shown to be involved in regulation of stem cells and cancer cells, CP-Geminin is expected to be useful for elucidating the role of Geminin in stem cells and cancer cells, and for manipulating their activity.